Transcendence and the Africana literary enterprise - Temple, Christel N. (Critical Africana studies., 2018)
Framing the concept of transcendence, this study covers over a dozen traditional African American works in an original and thought-provoking analysis that places canonical approaches in enlightened discourse with Africana studies reader-response priorities.